Propuesta de modelo de negocio forestal basado en un bosque secundario en el cantón de Turrialba, Cartago, Costa Rica - Quesada-Álvarez, Alejandro (Instituto Tecnológico de Costa Rica, 2018)
Secondary forests have become an important source for obtaining timber species, which is why the application of Executive Decree N ° 39952-MINAE and business models focused on the use of secondary forest is very important. In this paper, potential potential markets for the secondary forest and wood marketing chains in the Turrialba canton were analyzed, in order to generate a proposal for a business model based on secondary forest and the dominant species it offers Information was obtained to rule out potential markets such as the handicraft market, the market for the commercialization of carbon credits and there is a basis for further studies on the potential of the wood-based power generation industry. In addition, it was possible to find the importance of increasing the studies in terms of physical-mechanical properties of species not common in the market but abundant in secondary forests, as well as promoting their use and monopolizing an even larger market. It was determined that the model of The most viable business is the sale of sawn wood through portable sawmills in the farm yard and placing waste in the power generation industry, as well as obtaining data to determine that Executive Decree 39952-MINAE directly affects the profitability of secondary forests
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2018
Keywords: Modelo de negocios; Bosque; 39952-MINAE; Especies maderables; Aprovechamiento